Gambaran Epidemiologi Covid-19 Periode Januari-Juli 2021 di Puskesmas Cempaka Putih - Delia Maharani; Siti Maulidya Sari; Muhammad Arsyad (Jurnal Indonesia Sosial Sains, 2023)
Covid-19 is a disease caused by the SARS-CoV 2 virus and is highly contagious. Central Jakarta is one of the areas with the highest Covid-19 incidence, and the Cempaka Putih Health Center is one of the health centers in the area. This study used a descriptive study with secondary data in the form of medical records at the Cempaka Putih Health Center, and total sampling was obtained. This research resulted in (16%) aged <18 years, (42.4%) aged 18-40 years, (33, 6%) aged 41-64 years, (7.3%) aged ≥65 years, and (0.6%) not recorded. (46.5%) are male and (53.4%) are female. (12.6%) are employees, (4.2%) are students, (4.2%) are traders, others (4.4%), (1%) do not work, and (77.6% ) not recorded. Place of residence (47.5%) in Cempaka Putih District, (51.8%) outside of Cempaka Putih District, and (0.7%) not recorded. (15.4%) had a history of previous illness, (24.9%) had no history of previous illness, and (59.7%) were not recorded. (3.2%) had the COVID-19 vaccine, (7.3%) had never been vaccinated against COVID-19, and (89.5%) were not recorded. The conclusion of the study is that the highest proportion was obtained (42.4%) aged 18-40 years, (53.4%) women, (12.6%) employees, residence (51.8%) outside Cempaka District Putih, (24.9) had a previous history of illness, and (7.3%) had never received the COVID-19 vaccine. In the view of Islam one must stay away from the plague, and seek to get healed.